Environmental changes and macroinvertebrate responses in Patagonian streams (Argentina) to ashfall from the Chaitén Volcano (May 2008) - Miserendino, Maria Laura (2012)
On May 2nd of 2008 the Chaitén Volcano (Chile, 42°50′S and 72°39′W) erupted explosively producing a strong emission of volcanic ash. As a result of this eruption wide areas on the Argentinean side became covered by ashes. In order to investigate the effects of ashfall on environmental features, water quality and macroinvertebrate communities we conducted a study on 10 rivers affected by ash deposition in their hydrographic basins. Sites were visited seasonally (June 2008?March 2010) and results were compared with data obtained from previous research projects. Measures of pH, conductivity, oxygen content, main nutrients, and total suspended solids (TSS) were taken. Macroinvertebrate samples were obtained from riffles and pools. Community attributes were measured and metrics were calculated. A strong and significant increase in TSS values at most sites was recorded and although the peak diminished rapidly during the following months, resuspension and remobilization of ash continue even 20 months after. No significant changes in pH, conductivity and nutrients, comparing with data previous to the ashfall, were detected. Most rivers showed a strong diminution on macroinvertebrate density and richness, being small riversmore severely affected than the bigones. Correspondence analysis based on abundance data allows distinguishing preeruption from posteruption dates at five rivers. Density data and species richness showed low values in March of 2010, indicating that the community was not completely recovered at some sites. At least 25 taxa resulted significantly and negatively affected. Increased mortality could be related to several factors such as habitat deterioration, food quality diminution, interference with breathing mechanisms and with other physiological and morphological characteristics. Specific-taxa responses on the recolonization process were related to dispersal mech-anisms and specific strategies.